A Bitter Pill to Swallow? The Consequences of Patient Evaluation in Online Health Question-and-Answer Platforms - Chen, Chen; Walker, Dylan (Information Systems Research, 2023)
Online health question-and-answer platforms (OHQPs), where patients post health-related questions, evaluate advice from multiple doctors and select their most preferred answer, are a prominent channel for patients to receive medical advice in China. They are gaining traction globally and have the potential to circumvent resource-based, geographic, or circumstantial barriers that limit access to care. At the same time, they are underregulated in contrast to brick-and-mortar points of care. Ours is the first study to evaluate the quality of healthcare advice promoted by these platforms and to provide insight into how patients respond to advice. We found that, though advice is generally good, patients cannot discern good advice from bad, choose poor advice (when offered) as often as good advice, and do so to a greater extent in vulnerable categories such as pediatrics, cancers/tumors, and internal medicine. Moreover, we found that OHQPs exacerbate care avoidance. Our findings suggest that platform owners and policymakers should ensure that signals of expert consensus are provided to patients to better assist their choices on OHQPs. We also unveiled bad actors on OHQPs, including drug promoters and spammers, indicating that stronger oversight and accountability mechanisms are needed. Physician peer reviewing and auditing can address both problems.